Pengembangan Pembelajaran Melalui Media Ajilatu Dawwarah Al-Mufradat untuk Meningkatkan Hafalan Mufradat Siswa Madrasah Tsanawiyah Mambaus Sholihin Gresik - Anifah, Siti; Rizal, Hasan Syaiful; Hasyim, Mochamad (Impressive: Journal of Education, 2023)
This research is based on the needs of MTs. Mambaus Sholihin students to interactive learning media for more effective learning activities in memorizing mufradat and as an effort to increase the spirit of learning students. The objectives of this development study are: (1.) to know the influence of the use of AJIDAH learning media on the effectiveness of Mufradat memorization for students of grade VII-O MTs. Mambaus Sholihin Gresik, (2) knowing the significance of the impact of the development of AJIDAH learning media on the effectiveness of memorization of Mufradat students MTs. Mambaus Solihin Suci, Manyar, Gresik. This research is R and D research using quantitative approach, this type of research is Pre-Experimental Design with the form of One Group Pretest-Postest Design. The steps in this research method are: Needs Analysis, Data Collection, Product Design, Expert Review, Design Revision, Product Trial, Product Revision, Usage Trial, Product Revision, and Finished Product. Data obtained from observations, tests, interviews and documentation. Data analysis techniques use the "t" test. The results of this study are as follows: test results "t" against posttest learning results obtained thitung = 14.64 while ttabel with df 39 (40-1) at the level of significance 5% is 1.98. Thus 14.64 is greater than 1.98 which means the working hypothesis (Ha) in this study is accepted, namely the influence of the use of AJIDAH media on the effectiveness of memorization of Arabic vocabulary students MTs. Mambaus Sholihin, Gresik.